The need to linger: Can we change everyday discourse to enhance belonging in higher education? - Rudman, S. (South African Journal of Higher Education, 2022)
A student’s sense of belonging plays an important role in their overall experience and success at university. One of the factors which influence such a sense of belonging is the manner in which one is able to connect with those around one. On South African university campuses, student “connections” are often short-circuited by the tendency to “other” those from different ethnic / racial backgrounds. This happens despite the general abundance of “transformation talk” on campuses and much professed insight into issues of discrimination. This article considers the relationship between talk and authenticity with reference to Heidegger’s theory on the everydaynesss of discourse as well as his proposal that real understanding requires a willingness to “linger”. Content analysis of student reflections on a module which created an opportunity for students to “linger” with the “other” implies the potential which such spaces may have in facilitating “connections” otherwise perceived as unlikely.